2014
DOI: 10.1021/bi4016296
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bilayer Characteristics on the Structural Fate of Aβ(1–40) and Aβ(25–40)

Abstract: The β-amyloid (Aβ) peptide is derived from the transmembrane (TM) helix of the amyloid precursor protein (APP) and has been shown to interact with membrane surfaces. To understand better the role of peptide-membrane interactions in cell death and ultimately in Alzheimer's disease, a better understanding of how membrane characteristics affect the binding, solvation, and secondary structure of Aβ is needed. Employing a combination of circular dichroism and deep-UV resonance Raman spectroscopies, Aβ(25-40) was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…From Figure 5, it is apparent that fibrils can be formed at lipid surfaces at low Aβ concentration in the presence of Ca 2+ , and the fibril-accelerated conversion of monomers into cytotoxic oligomers can ultimately lead to membrane damage. 9 Recently, Xiong et al 82 suggest that insertion of Aβ(1−40) into lipid bilayers is followed by a conversion into the β-sheet structure, which forces the Cterminus out of the membrane for incorporating additional Aβ(1−40) molecules. However, in the presence of Ca 2+ , the Cterminus is stabilized and does not need to insert into the lipids to maximize the hydrophobic interaction or decrease the electrostatic repulsion.…”
Section: ■ Discussionmentioning
confidence: 99%
“…From Figure 5, it is apparent that fibrils can be formed at lipid surfaces at low Aβ concentration in the presence of Ca 2+ , and the fibril-accelerated conversion of monomers into cytotoxic oligomers can ultimately lead to membrane damage. 9 Recently, Xiong et al 82 suggest that insertion of Aβ(1−40) into lipid bilayers is followed by a conversion into the β-sheet structure, which forces the Cterminus out of the membrane for incorporating additional Aβ(1−40) molecules. However, in the presence of Ca 2+ , the Cterminus is stabilized and does not need to insert into the lipids to maximize the hydrophobic interaction or decrease the electrostatic repulsion.…”
Section: ■ Discussionmentioning
confidence: 99%
“…601 Aβ40 also behaved similarly to strongly adsorbed on anionic DLPG liposomes, with spontaneous structural transition from where it initially adopts mixtures of disordered and helical structures. 602 Furthermore, increased cholesterol in POPC bilayer promoted Aβ42 monomer with different conformations (i.e. α-helical and β-hairpin) to be adsorbed on the POPC bilayer, which further facilitated Aβ aggregation and membrane insertion (Figure 19d).…”
Section: Aβ40/42 and Its Mutantsmentioning
confidence: 99%
“…It was found that the peptide initially adopts mixtures of disordered and helical structures upon the interaction with anionic liposomes, which is followed by their conversion into β-sheet over longer timeframes. 71 …”
Section: Early Stages In Protein Aggregation Detection Of Prefibrilamentioning
confidence: 99%